Mordellid Beetles of the Genus Stenalia (Coleoptera, Mordellidae) of Central and Eastern Palaearctics. Communication 1 - Odnosum, V.K. (Вестник зоологии, 2000)
Using new characters (e. g., shape of the prothoracal disc, shape of the pygidium and its ratios comparing with the anal sternite, elytra and prothoracal disc, shape and armoury of the urosternite 8), a detailed diagnosis, a redescription and a key to males of 9 species of the genus Stenalia Mulsant are provided. Based upon study of type series, S. araxicola Khnzor. (lectotype designated) and S. ascaniaenovae Lazorko are redescribed. Morphological diagnoses of little-known species S. testacea (F.), S. brunneipennis Mulsant, S. iranica Horak, S. gracilicornis Baudi, S. escherichi Schilsky and S. bilyi Horak are improved. S. ermolenkoi sp. n. from Azerbaijan is described. The following synonymy is established: S. testacea (Fabricius, 1787) = S. dolini Lazorko, 1974, syn. n. The holotype of S. ermolenkoi sp. n., the lectotype of S. araxicola, the holotype and paratypes of S. ascaniaenovae are deposited at the Schmalhausen Institute of Zoology, National Academy of Sciences of Ukraine (Kyiv). Приведены краткая морфологическая характеристика родов Triteleia Kieffer, Paridris Kieffer и Calotelea Westwood, дополненные определительные таблицы палеарктических видов из этих родов, а также описания 4 новых видов: Triteleia asperitas Kononova, T. striolata Kononova et Petrov, Paridris stenus Kononova et Petrov, Calotelea striola Kononova. Типовой материал хранится в коллекции Института зоологии НАН Украины, 1 паратип Paridris stenus хранится в частной коллекции С. Петрова.